Expansion and Functional Divergence of the SHORT VEGETATIVE PHASE (SVP) Genes in Eudicots. (26th October 2018) - Liu, Xing; Sun, Zhichao; Dong, Wei; Wang, Zhengjia; Zhang, Liangsheng
Abstract: SHORT VEGETATIVE PHASE ( SVP ) genes are members of the well-known MADS-box gene family that regulates vital developmental processes in plants. In Arabidopsis, there are two SVP paralogs, SVP/AGAMOUS-LIKE22 ( SVP/AGL22 ) and AGL24 . SVP protein suppresses the flowering process, whereas AGL24 acts as a flowering activator. Phylogenetic analysis of SVP genes representing most of the sequenced eudicot species showed that the SVP gene family could be divided into three major clades in eudicots (SVP1, SVP2, and SVP3), most likely resulting from an ancient whole-genome triplication in core eudicots. Among them, the SVP1 (SVP) and SVP2 (AGL24) clades are retained in nearly all species, whereas the SVP3 clade has been lost in Brassicaceae, Myrtaceae, and some species in other families. Reflecting lineage-specific tandem duplication and whole-genome duplication, SVP gene copy numbers ranged from 3 to 11 in the analyzed species. Sequence analysis showed that SVP3 proteins have obvious differences with SVP1 and SVP2 in the C-terminal (C) domain and intervening (I) domain. Positive selection analysis also showed that the ω (d N /d S ) value was highest in the SVP3 clade, with 17 positive selection sites detected in the SVP3 clade. Promoter analysis for cis -regulatory elements showed that some genes in the SVP2 and SVP3 clades may be regulated by abscisic acid, ethylene, and gibberellin. RNA-seq data from grape, poplar, and apple revealed that genes in SVP3 group are highly expressed in vegetative organs such as buds, leaves, cotyledons, and dormant buds in particular, indicating the involvement of genes belong to SVP3 group in the dormancy process. Overall, the findings underscore the functional diversity of the SVP genes in eudicots.